Philosophy and Grand-Scale Politics from the Margins: Power and Corporeality Read through the Machiavelli of Gramsci - Aragón Moreno, Dante Ariel (International Gramsci Journal, 2024)
Drawing on Gramsci’s reading of Machiavelli, this article will use the philosophy of praxis and hegemony to account for the project of historicisation and corporeality of Gramscian philosophy in its political deployment. Through such a relationship, it will be possible to underline the collectively material and corporeal character of the Gramscian proposal in contrast to other traditional, speculative, elitist or political philosophies that are not organically related with the popular terrain. Thus, the Gramscian approach to philosophy proves very useful in confronting the political issues of the contemporary world, because of its capacity to promote democratic aspirations and the institution of a social and political alternative to the neo-liberal ethos. Finally, the relationship between the philosophy of praxis and popular culture will be reconsidered from a Latin American perspective.